Reproducibility of regional and global longitudinal strains derived from two-dimensional speckle-tracking and Doppler tissue imaging between expert and novice readers during quantitative dobutamine stress echocardiography - Yamada, A.; Luis, S.; Sathianathan, D.; Khandheria, B.; Cafaro, J.; Hamilton-Craig, C.; Platts, D.; Haseler, Luke; Burstow, D.; Chan, J. (2014)
Background: Longitudinal strain (LS) is a quantitative parameter that adds incremental value to wall motion analysis. The aim of this study was to compare the reproducibility of LS derived from Doppler tissue imaging and speckle-tracking between an expert and a novice strain reader during dobutamine stress echocardiography (DSE). Methods: Forty-one patients (mean age, 65 ± 15 years; mean ejection fraction, 58 ± 11%) underwent DSE per clinical protocol. Global LS derived from speckle-tracking and regional LS derived from both speckle-tracking and Doppler tissue imaging were measured twice by an expert strain reader and also measured twice by a novice strain reader. Intraobserver and interobserver analyses were performed using intraclass correlation coefficients (ICC), Bland-Altman analysis, and absolute difference values (mean ± SD). Results: Global LS measured by the expert strain reader demonstrated high intraobserver measurement reproducibility (rest: ICC = 0.95, absolute difference = 5.5 ± 4.9%; low dose: ICC = 0.96, absolute difference = 5.7 ± 3.7%; peak dose: ICC = 0.87, absolute difference = 11.4 ± 8.4%). Global LS measured by the novice strain reader also demonstrated high intraobserver reproducibility (rest: ICC = 0.97, absolute difference = 4.1 ± 3.4%; low dose: ICC = 0.94, absolute difference = 5.4 ± 5.9%; peak dose: ICC = 0.94, absolute difference = 6.1 ± 4.8%). Global LS also showed high interobserver agreement between the expert and novice readers at all stages of DSE (rest: ICC = 0.90, absolute difference = 8.5 ± 7.5%; low dose: ICC = 0.90, absolute difference = 8.9 ± 7.1%; peak dose: ICC = 0.87, absolute difference = 10.8 ± 8.4%). Of all parameters studied, LS derived from Doppler tissue imaging had relatively low interobserver and intraobserver agreement. Conclusions: Global LS is highly reproducible during all stages of DSE. This variable is a potentially reliable and reproducible measure of myocardial deformation.